Analysis of Quality of Life of Parents with Special Needs Children in Special Elementary Schools - Nisa, Nurul Hafizatun; Maidar, Maidar; Hermansyah, Hermansyah; Marthoenis, Marthoenis; Abdullah, Asnawi (GLOBAL HEALTH SCIENCE GROUP, 2025)
The quality of life of parents is an important thing in caring for children with special needs; it can be influenced by physical and emotional health. Health workers need to know the condition of the quality of life of parents to ensure the optimal care and intervention given. This study aims to analyze the quality of life of parents with children with special needs in special elementary schools in Banda Aceh City. The research design used is quantitative analytical with a cross-sectional design. The population in this study was 233 parents of Special Elementary School students in the Banda Aceh City area. Sampling using convenience sampling techniques, namely paying attention to inclusion and exclusion criteria. Data were collected using the World Health Organization Quality of Life questionnaire-BREF 27 (WHOQOL_BREF). Data analysis using logistic regression tests. The results showed that there was a relationship between the burden of caring for children (P=0.004), comorbidity (P=0.000), mental health depression (P=0.000), sleep quality (P=0.038), self-efficacy (P=0.000), education (P=0.024), employment (P=0.013), marital status (P=0.043) with the quality of life of parents with children with disabilities. At the same time, there was no relationship between mental health anxiety (P=0.650), stress (P=0.171), social support (P=0.457), family income (P=0.129), number of children (P=0.218) and gender of the child (P=0.218) with the quality of life of parents with children with disabilities. The most dominant variable influencing the quality of life of parents with children with disabilities is marital status. Single parents will be 5 times at risk of experiencing low quality of life compared to parents who raise their children with a complete family.